HUBUNGAN ASUPAN ZAT GIZI, POLA MAKAN DAN PENGETAHUAN GIZI DENGAN STATUS GIZI SANTRI DI PONDOK PESANTREN YATIM AT-THAYYIBAH SUKABUMI - Endah Nurwulan; Muhammad Furqan; Debby Endayani Safitri (UHAMKA PRESS, 2017)
Nutritional problems are complex that are influenced by direct and indirect factors.Nutrition intake, food pattern, and nutritional knowledge are factors that affect nutritionindirectly. Adolescents require good nutrition intake because at that time they areexperiencing growth both physically and physiologically, so inadequate intake will lead toslow growth. This study aimed to determine the relationship between nutrient intake, foodpattern, and nutritional knowledge with the nutrition status of santri at the At-ThayyibahIslamic Orphan Boarding School in Sukabumi. The study design in this study was crosssectional and the sampling technique used was purposive sampling with a total of 76 subjectsaged 13-18 years. From this study there was no significant relationship between nutrientintake (p> 0.05), diet (p> 0.05) and nutritional knowledge (p> 0.05) with nutritional status.